Liquid shampoo making from coconut oil with neem leaves (azadirachta indica) infused oil addition - Rini Nurul Fauziyah; Asri Widyasanti; Fitry Filianty (Agroindustrial Technology Journal, 2020)
The liquid shampoo is a preparation that generally used to clean hair and scalp from various kinds of impurities. Coconut oil is one of the raw materials for making shampoo which has many benefits, one ofwhich is the high lauric acid content. The additional active ingredient used in the liquid shampoo is neemleavesbecause the polyphenol content has antibacterial properties that are good for the scalp. Neem leaves infused oil is made by heat infusion with coconut oil as a solvent. The purpose of this study was to determine the effect of adding neem leaves infused oil on the quality of liquid shampoo produced. The concentration variation in the ratio of neem and coconut oil used was 20:160 (w/w). The method used in this research was a laboratory experiment with descriptive analysis. The results showed that the addition of neem leaves infused oil affected the yield of liquid shampoo is less (51,59%), the color of the shampoo, and the amount of foam produced.The analysis showed that all liquid shampoo treatments encounter the requirements of Indonesian National Standard (SNI) Shampo 06-2692-1992, namely organoleptic requirements (color, odor, and presence or absence of sediment) and shampoo pH (pH 5-9).